The other-race and other-species effects in face perception – a subordinate-level analysis - Dahl, Christoph D.; Rasch, Malte J.; Chen, Chien-Chung (Frontiers in Psychology, 2014)
The ability of face discrimination is modulated by the frequency of exposure to a category of faces. In other words, lower discrimination performance was measured for infrequently encountered faces as opposed to frequently encountered ones. This phenomenon has been described in the literature: the own-race advantage, a benefit in processing own-race as opposed to the other-race faces, and the own-species advantage, a benefit in processing the conspecific type of faces as opposed to the heterospecific type. So far, the exact parameters that drive either of these two effects are not fully understood. In the following we present a full assessment of data in human participants describing the discrimination performances across two races (Asian and Caucasian) as well as a range of non-human primate faces (chimpanzee, Rhesus macaque and marmoset). We measured reaction times of Asian participants performing a delayed matching-to-sample task, and correlated the results with similarity estimates of facial configuration and face parts. We found faster discrimination of own-race above other-race/species faces. Further, we found a strong reliance on configural information in upright own-species/-race faces and on individual face parts in all inverted face classes, supporting the assumption of specialized processing for the face class of most frequent exposure.